Correlating field and laboratory evolution of curing in cold in-place recycled (CIR) materials. (22nd August 2022) - Ogbo, Chibuike; Dave, Eshan V.; Sias, Jo E.; Zegeye, Eyoab
Highlights: Ground penetrating radar systems can be applied in moisture content evaluation of CIR pavements. Rapid compaction control device is applicable for monitoring strength evolution of CIR pavements.. Curing evolves faster in the field compared to the controlled lab conditions employed in this study. A strong relationship between the field and laboratory curing evolution times was established. Abstract: This study compared and explored the relationship between laboratory oven conditioning and field curing, using materials from six CIR projects and various field and laboratory testing procedures. The results indicate that the test methods considered in this study effectively tracked the curing process of laboratory and in-situ CIR materials. The data generated in the study provided good insight into the curing evolution of CIR materials and was employed to develop a robust relationship between the field and laboratory curing evolution times. Furthermore, the study introduced ground-penetrating radar (GPR) for continuous and repetitive monitoring of moisture content in CIR pavements.